Asymmetric Conflicts in the IR Theory: Contemporary Aspects of Studying - A. S. Teteruk; Y. A. Chizhevskiy (Сравнительная политика, 2015)
The authors are inclined to regard the potential of quantitative analysis that can be used for studying asymmetric conflicts.